Financial Performance Analysis to Assess the Financial Performance of Sharia Cooperative Arifin Achmad Hospital Pekanbaru Riau - Syarifah Nurfitriyana; Gusnardi Gusnardi; Hendripides Hendripides (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Research on the financial performance of cooperatives needs to be carried out in order to measure the success of cooperatives in generating profits, and to see the growth and development of these cooperatives. To evaluate the financial performance of cooperatives, the Indonesian government has made provisions for assessing ratios, which are contained in the Minister of Cooperatives and SMEs No.14/Per/M.KUKM/XII/2009. The purpose of this research is to see whether the Financial Performance of Sharia Cooperatives at RSUD Arifin Achmad Pekanbaru Riau has been effective in terms of financial ratio analysis based on the Regulation of the Minister of Cooperatives and SMEs of the Republic of Indonesia No. 14/Per/M.KUKM/XII/2009. The research method used is the quantitative method, while the results of the study are that there is a decrease in the total score of the overall score of the aspect ratio assessment each year. in the range of values between 40 ≤ x 60, it means that it is considered unhealthy. In 2018, if you look at the total score of the health assessment results of the Sharia Cooperative Arifin Achmad Pekanbaru Riau Hospital in 2018, it was 43.25, in the range of values between 40 ≤ x 60, means the criteria are not healthy. In 2019, if you look at the total score of the results of the health assessment of the Sharia Cooperative, Arifin Achmad Pekanbaru Riau Hospital in 2019, it was 41, in the range of values between 40 ≤ x 60, which means that it is considered unhealthy. Until 2020 and 2021 the health assessment of the Sharia Cooperative at Arifin Achmad Pekanbaru Hospital, Riau, continues to experience a decline from the previous year in the position of the criteria for being unhealthy to unhealthy. This can be seen from the total score obtained, in 2020 it was only 37.55 and 37.45 for 2021.